In the Lurch Verbatim Theater and the Crisis of Democratic Deliberation - Claycomb, Ryan (University of Michigan Press, 2023)
Some of theater's most powerful works in the past thirty years fall into the category of "verbatim theater," socially engaged performances whose texts rely on word-for-word testimony. Performances such as Fires in the Mirror, The Laramie Project, and The Vagina Monologues have at their best demonstrated how to hold hard conversations about explosive subjects in a liberal democracy. But in this moment of what author Ryan Claycomb terms the "rightward lurch" of western democracies, does this idealized space of democratic deliberation remain effective? In the Lurch asks that question in a pointed and self-reflexive way, tracing the history of this branch of documentary theater with particular attention to the political outcomes and stances these performances seem to seek. But this is not just a disinterested history-Claycomb reflects on his own participation in that political fantasy, including earlier scholarly writing that articulated with breathless hopefulness the potential of verbatim theater, and on his own theatrical attendance, imbued with a belief that witnessing this idealized public sphere was a substitute for actual public participation. In the Lurch also recounts the bumpy path towards its completion, two years marked by presidential impeachments, an insurrection, a national reckoning with racism, and a global pandemic. At the heart of the book is a central question: is verbatim theater any longer an effective cultural response to what can look like the possible end of democracy?